Health in the developing world: achieving the Millennium Development Goals - Jeffrey D. Sachs (The World Health Organization, 2004)
The Millennium Development Goals depend critically on scaling up public health investments in developing countries. As a matter of urgency, developing-country governments must present detailed investment plans that are sufficiently ambitious to meet the goals, and the plans must be inserted into existing donor processes. Donor countries must keep the promises they have often reiterated of increased assistance, which they can easily afford, to help improve health in the developing countries and ensure stability for the whole world.